ESL Teachers’ Attitude towards Intercultural Communicative Competence - Jusufi, Senad (Yearbook of the Department of Foreign Languages and Cultures, 2024)
Linguistic competence in language teaching has attracted the attention of many intercultural scholars. However, in the modern globalization era where people are technologically connected, equipping the learners with linguistic competence may not be the overall solution to ensuring intercultural communicative competence (ICC). Furthermore, appropriateness and effective communication are vital in providing an effective language learning process. This study has investigated the attitude of Prizren University EFL teachers towards promoting ICC in the classrooms and the strategies they employ in promoting the ICC. The study involved 35 Prizren University EFL teachers, full-time and part-time, with a teaching experience in different cultural backgrounds and who have mastered the course descriptions. The study employed structured questionnaire with open-ended questions. The questionnaire was divided into two major parts, with the first part seeking to find the attitude of the EFL teachers towards ICC in the classroom and the second part seeking to find out the strategies the participants used to promote ICC in the classrooms.